ANTIBACTERIAL ACTIVITY TEST OF WATER APPLE LEAF EXTRACT Syzygium aqueum (Burm.f) Alston AGAINST Salmonella typhi BACTERIA USING ELISA READER - Zulfiana, Salina; Azim, Muhlisun; Gemantari, Baiq Maylinda (UIN Mataram, 2024)
The water apple plant Syzygium aqueum (Burm. f) Alston is one of the plants used as traditional medicine due to its secondary metabolites such as flavonoids, steroids, terpenoids, alkaloids, tannins, phenols, saponins which can be utilized as antibacterials, antioxidants and others. This research aims to determine the IC50 antibacterial activity of the water apple leaf extract against Salmonella typhi ATCC-14028 bacteria in inhibiting bacterial growth. Extraction was carried out using multi-step maceration using n-hexane, ethyl acetate, and methanol as solvents to obtain the concentrated extracts. Antibacterial activity test was conducted by using the microdilution method on Mueller Hinton Broth media by calculating optical density (OD) values at concentrations of 500 ppm, 250 ppm, 125 ppm, 62.50 ppm, 31.25 ppm, 15.63 ppm, 7.831 ppm, and 3.906 ppm. The optical density value was measured at a wavelength of 595 nm by Elisa microplate reader. Phytochemical contents were investigated and the presence of flavonoid, phenol, steroid, and terpenoid compounds in the extracts was indicated. Water apple leaf extracts have antibacterial activity in inhibiting the growth of Salmonella typhi ATCC-14028 bacteria showing an IC50 value of n-hexane, ethyl acetate, and methanol extracts of 155,607 ± 30,592 µg/mL, 56.492 ± 50.124 µg/mL, 107.96 ± 50.124 µg/mL which is categorized as weak, strong, and moderate respectively.